A randomised trial of early palliative care for maternal stress in infants prenatally diagnosed with single-ventricle heart disease. (10th January 2018) - Hancock, Hayley S.; Pituch, Ken; Uzark, Karen; Bhat, Priya; Fifer, Carly; Silveira, Maria; Yu, Sunkyung; Welch, Suzanne; Donohue, Janet; Lowery, Ray; Aiyagari, Ranjit
Abstract: Children with single-ventricle disease experience high mortality and complex care. In other life-limiting childhood illnesses, paediatric palliative care may mitigate maternal stress. We hypothesised that early palliative care in the single-ventricle population may have the same benefit for mothers. In this pilot randomised trial of early palliative care, mothers of infants with prenatal single-ventricle diagnoses completed surveys measuring depression, anxiety, coping, and quality of life at a prenatal visit and neonatal discharge. Infants were randomised to receive early palliative care – structured evaluation, psychosocial/spiritual, and communication support before surgery – or standard care. Among 56 eligible mothers, 40 enrolled and completed baseline surveys; 38 neonates were randomised, 18 early palliative care and 20 standard care; and 34 postnatal surveys were completed. Baseline Beck Depression Inventory-II and State-Trait Anxiety Index scores exceeded normal pregnant sample scores (mean 13.76±8.46 versus 7.0±5.0 and 46.34±12.59 versus 29.8±6.35, respectively; p=0.0001); there were no significant differences between study groups. The early palliative care group had a decrease in prenatal to postnatal State-Trait Anxiety Index scores (−7.6 versus 0.3 in standard care, p=0.02), higher postnatal Brief Cope Inventory positive reframing scores (p=0.03), and a positive change in PedsQL Family Impact Module communication and family relationships scores (effect size 0.46 and 0.41, respectively). In conclusion, these data show that mothers of infants with single-ventricle disease experience significant depression and anxiety prenatally. Early palliative care resulted in decreased maternal anxiety, improved maternal positive reframing, and improved communication and family relationships.